Complete mitochondrial genome sequence and phylogenetic analysis of Lycodes polaris (Sabine, 1824). Issue 2 (3rd July 2019) - Li, Hai; Li, Yuan; Feng, Ji; Song, Puqing; Zhang, Nan; Lin, Longshan
Abstract: Lycodes polaris is one of the most widely distributed and abundant eelpout species on the Arctic continental shelves with full mitogenome information unavailable. In this paper, complete mitochondrial genome of L. Polaris was determined with 16, 595 bp in length, containing 13 protein-coding genes, 2 ribosomal RNA genes, 22 transfer RNA genes, and 2 non-coding regions (origin of light strand replication and control region). All the protein-coding genes choose ATG as start codon in addition to that COI using GTG. Most genes use TAA or TAG as the stop codon while three others ended with incomplete stop codons. Phylogenetic relationship of L. polaris was also reconstructed. Our result will provide important basis for further studies of L. polaris .